The Serum- and Glucocorticoid-Inducible Kinase 1 (SGK1) as a Novel Therapeutic Target in Mantle Cell Lymphoma. (29th November 2022) - Li, Jiao; Yu, Hui; Wang, Xing; Ye, Yingying; Fang, Wei; Ding, Ning; Mi, Lan; Ping, Lingyan; Wang, Xiaogan; Song, Yuqin; Zhu, Jun
Introduction: Mantle cell lymphoma (MCL) is an aggressive and incurable B-cell-derived malignant disease. MCL is treated using general chemotherapy; however, disease progression and relapse are common; thus, the development of novel therapeutic targets for treatment of MCL is urgently required. Serum- and glucocorticoid-inducible kinase 1 (SGK1) is involved in various cellular activities, and its dysregulation contributes to the pathogenesis of multiple types of cancer. However, little is known regarding its functional roles and associated molecular mechanisms in MCL. Methods: SGK1 inhibition mediated by either shRNA or treatment with SGK1 inhibitor (GSK650394) was conducted in MCL cell lines. Western blotting analysis was performed to figure out the expression of related proteins. MCL-cell-derived xenograft models were constructed to evaluate the anti-tumor effects of SGK1 inhibition or/and Bruton's tyrosine kinase (BTK) inhibition in vivo. Results: In this study, it was shown that inhibition of SGK1 significantly reduced cell proliferation, invasion and migration, increased apoptosis and blocked cell cycle progression in MCL cells. Furthermore, SGK1 inhibition significantly reduced the activation of ERK, AKT/mTOR, JAK2/STAT3 and the NF-κB signaling pathways. Using MCL-cell-derived xenograft mice models, SGK1 inhibition decreased tumor cell proliferation and tumor growth. Importantly, SGK1 overexpression significantly promoted xenograft tumor growth. Moreover, simultaneous inhibition of SGK1 and Bruton tyrosine kinase (BTK) resulted in synergistic anti-tumor effects on MCL both in vitro and in vivo. Conclusion: SGK1 may be a novel candidate therapeutic target and simultaneous inhibition of SGK1 and BTK may be a promising therapeutic strategy for MCL patients. Further pre-clinical and even clinical studies of SGK1 inhibitor or combination with BTK inhibitor are essential.